2017
DOI: 10.14569/ijacsa.2017.081001
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Gamification in Higher Education: An Empirical Study

Abstract: Abstract-The use of gamification in higher education has increased considerably over the past decades. An empirical study was conducted in Hungary with two groups of students to investigate their behaviour while interacting with Kahoot! The results were analyzed based on the technology acceptance model. They indicate that the positive attitude, good experience and ease of availability contributed to improve student performance which strengthened the intention to use the application. Besides these, the perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 10 publications
0
43
0
2
Order By: Relevance
“…For example, in many fields such as physics, chemistry, engineering, computer sciences and medicine or pharmacy, the studies found that kahoot could create motivation of the students This study, provided more information about effect of the 8 learning skills that similar to previous studies which evaluated only knowledge skill (literacy). [1][2][3][4][5] Study of Micaela Esteves et al supported about the advantages of kahoot web based learning. 6 Consider about the consistency effect of kahoot web-based leaning, the second generation was tested in this study (Year 2017), It found the similar effect as same as previous generation of students (Year 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in many fields such as physics, chemistry, engineering, computer sciences and medicine or pharmacy, the studies found that kahoot could create motivation of the students This study, provided more information about effect of the 8 learning skills that similar to previous studies which evaluated only knowledge skill (literacy). [1][2][3][4][5] Study of Micaela Esteves et al supported about the advantages of kahoot web based learning. 6 Consider about the consistency effect of kahoot web-based leaning, the second generation was tested in this study (Year 2017), It found the similar effect as same as previous generation of students (Year 2016).…”
Section: Discussionmentioning
confidence: 99%
“…can provide learners with additional intrinsic motivation. Varannai, Sasvári, & Urbanovics (2017) pointed that gamification through Kahoot! sustainably motivates learners preventing absence in lectures and seminars.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, Digital natives can no longer be motivated with traditional instructional tools (Premarathne, 2017), and this new generation grows more familiar with the technology (Özdemir, 2017). This generation has been born to a digitalized world thus smart tools are inevitable parts of their daily life (Varannai, Sasvári, & Urbanovics, 2017).…”
Section: The Rise Of Digital Assessment Toolsmentioning
confidence: 99%
“…The implementation of gamification methods and social media is to increase student participation in learning for emergency medicine in the world of health [18]. The effect of the gamification learning model also shows a positive attitude towards groups of students due to learning [19].…”
Section: Related Workmentioning
confidence: 99%